Research Synthesis of the Components of a Sexuality Education Curriculum - Vazie, Mojtaba; Yari, Jahangir; Adib, Yousef (Assessment and Practice in Educational Sciences, 2026)
The objective of this study was to synthesize existing research to identify and systematize the core components of a comprehensive sexuality education curriculum within an integrated curriculum framework. This study employed a qualitative research synthesis methodology with an applied, cross-sectional design. The research corpus consisted of peer-reviewed journal articles, master’s theses, doctoral dissertations, and scholarly books published between 2015 and 2025 in both domestic and international contexts that addressed sexuality education, sexuality education curricula, or related instructional programs. A total of 60 sources meeting predefined inclusion criteria were selected through systematic database searches. Data were analyzed using qualitative content analysis based on thematic coding. Following open, axial, and selective coding procedures, extracted concepts were organized and synthesized using Akker’s ten-element curriculum framework, encompassing rationale, objectives, content, learning activities, teacher role, resources, grouping, place, time, and evaluation. The synthesis identified 100 distinct curriculum components, which were systematically classified into ten interrelated curriculum elements. The results indicate that effective sexuality education curricula are multidimensional systems rather than content-focused interventions. Key inferential patterns suggest that curriculum coherence depends on the alignment of culturally grounded rationales, prevention- and development-oriented objectives, competency-based content, participatory learning activities, well-prepared teachers, diversified resources, flexible grouping strategies, multiple learning environments, developmentally sequenced timing, and multidimensional evaluation mechanisms. Fragmentation or omission of these elements was inferred to weaken curriculum implementation and sustainability. The findings demonstrate that sexuality education should be conceptualized and managed as an integrated curriculum system. The synthesized framework provides evidence-based guidance for curriculum developers, policymakers, and educators seeking to design, implement, and evaluate coherent and contextually responsive sexuality education programs.